Day and Night Thermal Analysis of a Low, Medium and High Load - Abdul Rahim, Nur Aqilah Aliah; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2023)
Thermal scanning in electrical maintenance is an important method for calculating temperature and heat transfer within and between electrical system components and their surroundings. Black box or pole fuse switch is ranked as having the second-highest breakdown due to the delay in recognizing that there has been a temperature change occur. The inspection procedure is usually conducted solely in accordance with the schedule and does not include a set period of time for thermography scanning. The objective of this project is to determine the best time for thermography scanning of low-voltage poles by measuring temperature differentials and simulating the results with the Fluke SmartView software. The data is collected in three categories of load (low, medium, and high) and measured in degrees Fahrenheit using a thermal imaging camera. The collected data is analyzed to provide guidance for efficient scanning. Data was gathered using a thermography scanner, and Smart FlukeView software is also used for simulation. The proper time, either daytime or night, for thermography scanner thermal analysis of low voltage poles is established after analysis of all data collected during thermal analysis to ensure the correctness of each inspection condition. The results of thermography scanning for thermal inspection for the black box or pole fuse switch are suggested to be done at night. Thermal analysis results found that all the results’ accuracy ranges from 87.7% to 97.4%. Furthermore, the inspection results are 93.9% accurate overall. Lastly, this project can assist in doing preventative maintenance earlier and avoiding consumer brief power outages.